Unifying Physics of Accelerators, Lasers and Plasma - Seryi, Andrei (Taylor & Francis, 2016)
Unifying Physics of Accelerators, Lasers and Plasma introduces the physics of accelerators, lasers and plasma in tandem with the industrial methodology of inventiveness, a technique that teaches that similar problems and solutions appear again and again in seemingly dissimilar disciplines. This unique approach builds bridges and enhances connection